(untitled) (Annals of Medical Research, 2022)
Aim: Systemic lupus erythematosus (SLE) is the prototype of chronic autoimmune diseases. One-fifth of all SLE disease occurs in childhood. In this study, it was aimed to compare the SLE classification criteria that have been used so far. These are the ACR (American College of Rheumatology) 1997, SLICC (Systemic Lupus International Collaborating Clinics) 2012, and EULAR (European League against Rheumatism) / ACR 2019 criteria. Materials and Methods: Patients with 34 pediatric SLE and 32 antinuclear antibodies (ANA) (+) control groups who were followed up in Ankara Dr. Sami Ulus Obstetrics and Children’s Hospital Pediatric Rheumatology Clinic were recruited to study. All of these patients were diagnosed by three pediatric rheumatologists. The control group consisted of ANA (+) patients with other rheumatologic diseases. Results: The sensitivities of the ACR 1997, SLICC 2012, and EULAR/ACR 2019 criteria were 76.5%, 94.1%, and 88.2%, respectively. The specificities of the criteria for ACR 1997, SLICC2012, and EULAR/ACR 2019 were 93.8%. Conclusion: Although SLICC 2012 showed the best sensitivity, all three classification criteria had the same specificity.